The size of indirect financial distress costs: which variable is reliably important? / Norhisam Bulot, Norhana Salamudin and Rasyidah Abd Aziz - Bulot, Norhisam; Salamudin, Norhana; Abd Aziz, Rasyidah (Universiti Teknologi MARA, Perlis, 2017)
In this paper, we analyze a panel data of 190 financially distressed firms to determine which firm-specific variable is reliably important in explaining the level of indirect financial distress costs. A better understanding of factors affecting indirect financial distress costs is essential not only for the purpose of enriching empirical studies in this field but also for the purpose of cross-country comparison. Optimal model selection procedure, together with panel data analysis technique is used to determine the most optimal model to explain the level of indirect financial distress costs. The findings of this paper indicate that the average size of the indirect financial distress costs for the period of study is 21.6%. In addition to that, this paper finds evidence suggesting the relevance of size of the firm, the level of intangible assets and the existence of alternative investment opportunities, which implies the importance of these factors in determining the level of indirect financial distress costs. This paper argues that the level of liquid assets and expected earnings growth are statistically unimportant in determining the level of indirect financial distress costs for Malaysia's financially distressed firms